Politics of Subaltern Consciousness: The Substantive Representation of the Margins in Nehru’s Toward Freedom and Roy’s The Ministry of Utmost Happiness - Awasthi, Prabeen Kumar (Literary Studies, 2022)
Despite being placed at the bottom of the society, Indian subalterns have always gained central position in the political sphere. This paper investigates the substantive representation of marginalized groups and the way they employ their consciousness to dismantle injustices by analyzing Jawaharlal Nehru’s autobiography Toward Freedom (1936) and Arundhati Roy’s novel The Ministry of Utmost Happiness (2017). The subaltern struggle in the society in the quest of their autonomous self and it is achieved with the help of continuous resistance on their part. Colonized Indians display their resistance to counter the British Raj. In the like manner, Hijras, women and Dalits resist the conventional norms of the mainstream by developing anti-normative body and by adopting new roles in the society. Delving on Antonio Gramsci, Gayatri Chakravorty Spivak, and Ranajit Guha’s ideas of the subaltern, this study analyzes the life of the colonized Indians, the transgender, and the untouchables located in the periphery of social, economic and political strata of the colonial and the post-millennial India. Besides the Subaltern Studies’ scholars, Tamen and Garnett’s notion on ‘self,’ ‘interpretation,’ ‘agency’ and ‘resistance’ have been applied to show the way subalterns overcome their subordination in the existing social order. From the standpoint of Nehru’s promise, this study critiques the politics and the position of the subaltern in the first decade of the twentieth century as presented in Roy.